Case Report: Residual Atrial Shunt Lesions in Aging Adults With Congenital Heart Disease: An Underestimated Risk of Stroke? - Schneider, Matthias; Dannenberg, Varius; Opgen-Rhein, Bernd; Berger, Felix; Pieske, Burkert; Gabriel, Harald; Boldt, Leif-Hendrik (Frontiers in Cardiovascular Medicine, 2022)
We report two cases of paradoxical cerebral embolism in adults with congenital heart disease (ACHD) with residual atrial shunt lesions, a 59 year-old male patient with partial detachment of a surgical ASD closure patch, and a 57 year-old male patient with Ebstein’s anomaly and a large patent foramen ovale. Considering these mechanisms and the increasing incidence of venous thrombosis with age, a higher prevalence of paradoxical embolism in ACHD patients with residual atrial shunts may be suspected. Conclusion: Regular follow-up of patients with ACHD remains important throughout life even in seemingly stable lesions.